Gatekeeping Reconciliation: The Supreme Court of Canada’s Piecemeal Erosion of Aboriginal Rights - Al-Noman, Haneen (Ottawa Law Review / Revue de droit d’Ottawa, 2022)
This paper engages critically with the Supreme Court of Canada’s jurisprudence on section 35 to demonstrate that the Court has narrowed the scope of Aboriginal rights and broadened the Crown’s power to infringe on recognized rights. It focuses on the Court’s view that protected Aboriginal rights must find their roots in integral and distinctive pre-contact practices. By focusing on the challenges of meeting this test, this paper demonstrates that the Court’s framework is onerous and ahistorical.The paper also situates the Court’s jurisprudence in the broader context in which section 35 was drafted. It relies in part on this contextual analysis to argue that the Court’s framework has impeded the objective of section 35—reconciliation of Aboriginal societies with Crown sovereignty. More specifically, the author shows that the Court’s interpretation provides the Crown with an unfair advantage—one often used as leverage in negotiations with Aboriginal communities. This advantage hollows section 35 and erodes its efficacy.Finally, the paper explores other possible frameworks through which the Court may interpret section 35 and then responds to common concerns that have been expressed to prevent the pursuit of those alternatives. The paper uses section 23’s protection of minority language rights as an analogy to aid in advancing our understanding of section 35’s proper scope. The author concludes that the relatively broad section 23 rights and the narrow infringement power in section 1 of the Charter provide a pragmatic model that can govern the rights protected by section 35 and help push reconciliation forward.